Penatalaksanaan Awal Takikardia Supraventrikular Paroksismal dengan Depresi Segmen ST pada Pengaturan Perawatan Primer: Laporan Kasus - Kevin Fernando Suhardi; Franky Kurniawan; Lusiani (PT Kalbe Farma Tbk., 2025)
Introduction: Supraventricular tachycardia (SVT) is a common cardiac emergency that can be life-threatening. Symptoms may include palpitations, chest pain, and difficulty breathing. Case: A 50-year-old male with sudden palpitations since one hour ago, accompanied by chest pain and breathing difficulty. A 12-lead ECG revealed an SVT rhythm with ST-segment depression in leads II, III, aVF, and V2-V6. After initial interventions, which included carotid massage, Valsalva maneuver, and oral bisoprolol, the rhythm converted to sinus rhythm within an hour. ST-segment depression may occur during SVT, which warrants evaluation for ischemic etiology. Conclusion: The report focuses on the initial management of SVT in a primary care setting with constraints on equipment and referral facilities. It's important to note that changes in the ST segment in SVT do not always indicate myocardial infarction, and further examination is necessary to confirm the diagnosis.